Unravelling the hidden struggles: the impact of neurofibromatosis on adolescent mental health and well-being - Parikh, Parinda; Sir, Dilbeste (International Journal Of Community Medicine And Public Health, 2025)
Neurofibromatosis type 1 (NF1) is a genetic disorder characterized by benign tumors and various psychosocial challenges, particularly in adolescents. This case vignette details a 14-year-old female with NF1 who presents with significant academic struggles, emotional instability, and social withdrawal, exacerbated by bullying and low self-esteem. Despite a comprehensive medication regimen, including Gabapentin, Methylphenidate, Aripiprazole, and Sertraline, her symptoms persist, highlighting the complexity of managing NF1’s multifaceted impact. The interplay between her physical condition and psychiatric manifestations underscores the necessity for a holistic management approach that integrates medical treatment with targeted psychiatric support. This case emphasizes the importance of early identification and intervention for mental health issues in adolescents with NF1, advocating for multidisciplinary strategies that involve healthcare providers, mental health professionals, and families to enhance overall quality of life and facilitate effective coping mechanisms. Further research is essential to refine management practices and address the unique needs of this population.